Group G streptococcal pneumonia and sepsis in a newborn infant. - Ancona, R J (1979)
A case of neonatal pneumonia and sepsis caused by a group G Streptococcus is described. Clinical and microbiological aspects of group G streptococci are compared with those of group B streptococci.